Expansion and evolution of the X-linked testis specific multigene families in the melanogaster species subgroup. - Galina L Kogan; Lev A Usakin; Sergei S Ryazansky; Vladimir A Gvozdev (PLoS ONE, 2012)
The testis specific X-linked genes whose evolution is traced here in the melanogaster species subgroup are thought to undergo fast rate of diversification. The CK2ßtes and NACβtes gene families encode the diverged regulatory β-subunits of protein kinase CK2 and the homologs of β-subunit of nascent peptide associated complex, respectively. We annotated the CK2βtes-like genes related to CK2ßtes family in the D. simulans and D. sechellia genomes. The ancestor CK2βtes-like genes preserved in D. simulans and D. sechellia are considered to be intermediates in the emergence of the D. melanogaster specific Stellate genes related to the CK2ßtes family. The CK2ßtes-like genes are more similar to the unique autosomal CK2ßtes gene than to Stellates, taking into account their peculiarities of polymorphism. The formation of a variant the CK2ßtes gene Stellate in D. melanogaster as a result of illegitimate recombination between a NACßtes promoter and a distinct polymorphic variant of CK2ßtes-like ancestor copy was traced. We found a close nonrandom proximity between the dispersed defective copies of DINE-1 transposons, the members of Helitron family, and the CK2βtes and NACβtes genes, suggesting an involvement of DINE-1 elements in duplication and amplification of these genes.